Specific relief act[1 of 1877] (Dhaka : Bangladesh Law Chronicles, 2007)
Reference work of Bangladesh Law Chronicles.
Keywords: Criminal procedure -- Bangladesh -- Digests; Criminal law -- Bangladesh -- Digests